2010
DOI: 10.1038/nmat2883
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalysts for the hydrogen oxidation and oxygen reduction reactions by patterning of platinum with calix[4]arene molecules

Abstract: The design of new catalysts for polymer electrolyte membrane fuel cells must be guided by two equally important fundamental principles: optimization of their catalytic behaviour as well as the long-term stability of the metal catalysts and supports in hostile electrochemical environments. The methods used to improve catalytic activity are diverse, ranging from the alloying and de-alloying of platinum to the synthesis of platinum core-shell catalysts. However, methods to improve the stability of the carbon supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 28 publications
10
150
1
Order By: Relevance
“…Although some basic research is carried out on this topic [50], up to now no durable catalyst could be found. iii)…”
Section: Ecs Transactions 45 (2) 3-14 (2012)mentioning
confidence: 99%
“…Although some basic research is carried out on this topic [50], up to now no durable catalyst could be found. iii)…”
Section: Ecs Transactions 45 (2) 3-14 (2012)mentioning
confidence: 99%
“…27 The structure of a calix [4]arene thiol derivative that they used is illustrated in Figure 2a. The wide rim containing sulfur atoms can firmly adsorb onto the Pt(111) terrace, leaving some edge or step sites (i.e., natural defects) and narrow terraces between the calix [4]arene [4]arene molecules totally suppress the oxygen adsorption/desorption (+0.5 ~ +0.9 V), and most of hydrogen adsorption/desorption (+0.05 ~ +0.4 V), as their coverage increases from 0.84 to 0.98 (from curve A to D).…”
Section: Modification Of Pt Single Crystal Planes With Calix[4]arenementioning
confidence: 99%
“…The observed exceptional selectivity is not unique to the Pt(111)-calix system and has also been observed on Pt(100) and polycrystalline Pt electrodes, as well as Pt nanoparticles. 27,28 The successful preparation of oxygen-tolerant Pt catalysts for HOR indicates that surface functionalization of Pt surfaces is a promising approach to tuning the selectivity of electrocatalysts, which has great applications such as methanol-tolerant ORR catalysts.…”
Section: Modification Of Pt Single Crystal Planes With Calix[4]arenementioning
confidence: 99%
“…Cavities are potential sites for sieving cations with small ionic radius such as H + or Li + . [21][22][23] The letter is relevant to the enhanced accessibility of the active species in the energy conversion and storage systems. The crucial step in synthetic routes was the introduction of anchor functional groups.…”
Section: Introductionmentioning
confidence: 99%